Réponses

2014-01-22T22:10:28+01:00
Bonsoir

1) factoriser (X-2)²-4x8²   

(x - 2)² - 4*8² = (x - 2)² - 2² * 8²
                      =[(x - 2) - 2*8][(x - 2) + 2*8] 
                      =(x - 2 - 16)(x - 2 + 16)
                      =(x - 18)(x + 14)
 
2) 3²X²-2x3x2X+2²=(3²X²)-2x3x2X+2² 

3² * x² - 2 * 3 * 2x + 2² = (3x)² - 2 * (3x) * 2 + 2²
                                     = (3x - 2)²

3) factoriser (3X-2)-(8X+3)(3X-2)+(3X-2)²

(3x - 2) - (8x + 3)(3x - 2) + (3x - 2)² =1*
(3x - 2) - (8x + 3)(3x - 2) + (3x - 2)(3x - 2)
                                                          = (3x - 2)[1 - (8x + 3) + (3x - 2)] 
                                                          = (3x - 2)(1 - 8x - 3 + 3x - 2)
                                                          = (3x - 2)(-5x - 4)